Perspektif Guru Bahasa Indonesia Dalam Kebijakan Merdeka Belajar Di SMK Negeri 2 Bengkulu Tengah - Gumono; Liza Oknasari; Dian Eka Chandra Wardhana (Manajer Pendididikan, 2023)
The purpose of this research is to find out the perspective of Indonesian language teachers in the Freedom to Learn Policy at SMK Negeri 2 Bengkulu Tengah. Data collection techniques used documentation and interviews regarding the Freedom to Learn Policy which consisted of four main points, namely school assessment, competency assessment, simplification of lesson plans, and zoning-based new student admissions. Data analysis techniques with stages, namely data collection, data transcription, data identification, data classification, data verification, and drawing conclusions. The results of this study are (1) Indonesian language teachers have a good perspective on the Freedom of Learning Policy as the subject of school assessment, but the implementation of school assessments still needs improvement according to the Freedom of Learning Policy, (2) Indonesian teachers have a good perspective on Policy Merdeka Learning is the subject of competency assessment and its implementation is in accordance with the Implementation of the 2022 National Assessment, (3) Indonesian language teachers have a good perspective on the Merdeka Learning Policy on the subject of simplifying lesson plans, but teachers still use lesson plans in K.13 format, and (4) Indonesian language teachers have a perspective that is less supportive of the implementation of Zoning-based student admissions in the Freedom to Learn Policy.